2022
DOI: 10.3390/ijms23126542
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Antidiabetic Drugs in Treating Dementia: A Peek into Pharmacological and Pharmacokinetic Properties

Abstract: Dementia dramatically affects the activities of daily living and quality of life; thus, many therapeutic approaches for overcoming dementia have been developed. However, an effective treatment regimen is yet to be developed. As diabetes is a well-known risk factor for dementia, drug repositioning and repurposing of antidiabetic drugs are expected to be effective dementia treatments. Several observational studies have been useful for understanding the effectiveness of antidiabetic drugs in treating dementia, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 94 publications
0
17
0
Order By: Relevance
“…A large number of preclinical studies in vivo and in vitro have demonstrated the potential protective effects of TZDs on dementia. TZDs can penetrate the blood–brain barrier, especially pioglitazone 8 . They can activate PPAR‐γ, which are expressed in various regions of the brain, regulating a range of activities that positively influence the pathology of Alzheimer's disease, including reducing insulin resistance, inhibiting inflammation, improving mitochondrial function, and reducing tau and amyloid pathology 9,30,31 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A large number of preclinical studies in vivo and in vitro have demonstrated the potential protective effects of TZDs on dementia. TZDs can penetrate the blood–brain barrier, especially pioglitazone 8 . They can activate PPAR‐γ, which are expressed in various regions of the brain, regulating a range of activities that positively influence the pathology of Alzheimer's disease, including reducing insulin resistance, inhibiting inflammation, improving mitochondrial function, and reducing tau and amyloid pathology 9,30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent large‐scale cohort study conducted in Korea found that in T2DM patients receiving metformin‐based dual oral therapy, use of metformin + TZDs and sulfonylureas + TZDs could significantly reduce the risk of all‐cause dementia by 20% and 4% respectively compared with use of metformin + sulfonylureas 33 . Variation in the magnitude of HRs could be due to different comparators, as some evidence indicated that metformin and sulfonylurea might also have effects on dementia risk 8,34 . Lu et al applied a matching strategy to investigate the use of antidiabetic drugs and dementia risk in the Chinese population living in Taiwan 31 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations